Menafsir Ulang “Roh Antikristus” dalam 1 Yohanes 4:1-6: Dari Spekulasi Eskatologis Menuju Pengujian Kristologis - Katu, Jefri Hina Remi (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2025)
The spirit of the Antichrist is often interpreted literally as an eschatological enemy of Christ who will persecute the church near the end of history. This interpretation, which remains influential in some Pentecostal settings, commonly treats the appearance of the Antichrist as a sign of the end times. Yet the term antichrist occurs only in the Johannine Letters and not elsewhere in the New Testament. This article therefore exegetes 1 John 4:1-6 in its historical and literary contexts to reconsider the identity of the “spirit of the Antichrist.” It argues that the phrase does not primarily denote a future eschatological being, but a present reality manifested in teaching that denies the true identity of Jesus Christ and, consequently, in conduct that contradicts his command to love. The passage thus calls the church to discern false teaching and to recognize that the antichrist spirit may operate both outside and within the Christian community.